Niemann-Pick Disease Type C Presenting as a Developmental Coordination Disorder with Bullying by Peers in a School-Age Child. (16th December 2015) - Suzuki, Ryo; Tanaka, Atsushi; Matsui, Toshiharu; Gunji, Tetsuki; Tohyama, Jun; Nairita, Aya; Nanba, Eiji; Ohno, Kousaku
Abstract : Niemann-Pick disease type C (NPC) is a rare progressive neurodegenerative disorder, often with onset after normal early childhood development. Juvenile onset NPC patients slowly develop cerebellar symptoms and cognitive impairment and often experience difficulties at school. However, these problems may be overlooked due to the unpublicized nature of NPC, given that it is a rare metabolic disorder. In this report, we present an 11-year-old male NPC patient, who suffered from clumsiness and difficulties in attention and academic and social skills. His symptoms were initially considered to be due to developmental coordination disorder (DCD) coexisting with bullying by peers. DCD is a type of neurodevelopmental disorder defined according to DSM-IV and is characterized by clumsiness that interferes with academic achievement and social integration not due to other general medical conditions. However, a detailed investigation of the patient suggested that the problems could be attributed to the onset of NPC. Clinicians should keep neurodegenerative disorders as differential diagnosis of children with multiple school problems.